Sustainable Agriculture Reviews 32 Waste Recycling and Fertilisation (Sustainable Agriculture Reviews, 2018)
This book summarise advanced knowledge and methods to recycle waste and fertilise soils in agriculture. In the near future, waste recycling will no longer be an option because natural resources become rare and costly, urbanisation is blooming and population is growing. In theory, most waste could be recycled. In practice, most waste is wasted. Remarkable aspects include the concepts of waste hierarchy eco-houses in smart cities, microbes and fungi for plant nutrition, and benefits of legume cultivation, biochar application and agropastoralism.